Lowinson and Ruiz's substance abuse : a comprehensive textbook. - Ruiz, Pedro, 1936-; Strain, Eric C.; Lowinson, Joyce H. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"A comprehensive, authoritative text on all aspects of substance abuse and addiction medicine. Scientific topics such as the biology of various addictions and all dimensions of clinical treatment and management are addressed by a wide range of leading contributors. Behavioral addictions are addressed also, so the text is not solely devoted to specific substances and their misuse"--Provided by publisher.
section 1. Foundations -- section 2. Determinants of abuse and dependence -- section 3. Evaluation -- section 4. Substances of abuse -- section 5. Compulsive and addictive behaviors -- section 6. Treatment approaches -- section 7. Management of associated medical conditions -- section 8. Models of prevention -- section 9. Life cycle -- section 10. Special populations -- section 11. Training and education -- section 12. Policy issues.
Rev. edition of: Substance abuse / editors, Joyce H. Lowinson [and others]. 4th edition c2005.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Substance abuse; Substance abuse -- Treatment; Substance abuse -- Social aspects; Electronic books